Legume Seed Nutraceutical Research - Jimenez-Lopez, Jose C.; Clemente, Alfonso (IntechOpen, 2019)
Legumes are a main source of nitrogen-rich edible seeds and constitute a major source of food for a significant part of the world's population. Particularly, they are the most relevant sources of plant proteins with nutraceutical and health benefit properties. This book was conceived to provide key research knowledge on health-promoting aspects of seed components, and their nutritional and nutraceutical values, for increasing awareness among the population of the research focus across the growing field of legume research, and the area of sustainable crop production.